2008
DOI: 10.2209/tdcpublication.49.89
|View full text |Cite|
|
Sign up to set email alerts
|

Treatment of Intrabony Periodontal Defects with Enamel Matrix Derivative in Private Practice: A Long-term Retrospective Study

Abstract: The present study describes treatment of intrabony periodontal defects with enamel matrix derivative (EMD) in private practice. Ten patients with clinical diagnosis of chronic periodontitis were subjected to data analysis. A total of 18 teeth with various osseous defects received regenerative therapy with EMD, and were followed for a minimum of 2 years. Treatment of the intrabony defects with EMD led to a statistically significant improvement in the mean value of probing depth at 1-year when compared with at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 19 publications
(18 reference statements)
2
9
1
1
Order By: Relevance
“…This gain was comparable with that observed in our earlier study in a private practice setting 15) . A meta analysis of clinical studies on the management of angular osseous defects with EMD 7) revealed a reduction in PD of 4.0 mm (50% of the baseline PD) and gain in CAL of 3.2 mm (33% of the original attachment level) in a total of 317 lesions over an observation period ranging from 6 to 12 months.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This gain was comparable with that observed in our earlier study in a private practice setting 15) . A meta analysis of clinical studies on the management of angular osseous defects with EMD 7) revealed a reduction in PD of 4.0 mm (50% of the baseline PD) and gain in CAL of 3.2 mm (33% of the original attachment level) in a total of 317 lesions over an observation period ranging from 6 to 12 months.…”
Section: Discussionsupporting
confidence: 91%
“…Interventions ranged from localized to quadrant surgery, with at least one tooth in the quadrant having intrabony defects matching the above-mentioned criteria. Regenerative therapy with EMD was performed at 25 sites (17 molars, 3 premolars, 3 canines, and 2 incisors) in 13 patients by the standard procedure as described previously 15) . Briefly, a full-thickness periodontal flap (papilla preservation technique) was employed to gain access to the root surface for scaling and root planing.…”
Section: Periodontal Regenerative Therapymentioning
confidence: 99%
“…In their international multi-center study, Tonetti et al 21) reported a mean CAL gain of 3.1 mm at 1 year. Previous study by our group evaluated the long-term clinical outcomes of treatment with EMD in a private practice setting 17) . The mean CAL gain at 6 months was 3.6 mm, which was significantly greater than that (2.2 mm) observed in our study on guided tissue regeneration utilizing bioresorbable membrane 26) .…”
Section: Discussionmentioning
confidence: 99%
“…Interventions ranged from localized to quadrant surgery, with at least one tooth in the quadrant having intrabony defects matching the abovementioned criteria. Regenerative therapy with EMD was performed by the standard procedure as described previously 17) . Briefly, a fullthickness periodontal flap (papilla preservation technique) was employed to gain access to the root surface for scaling and root planing.…”
Section: Periodontal Regenerative Therapymentioning
confidence: 99%
“…Our results that the EO + E had no inhibitory effects on the early behaviors of gingival epithelial cells may in part support such findings. In our previous clinical study, the EO + E mouthrinse was introduced as a patient home care regimen following periodontal regenerative therapy (Saito et al, 2008). The postoperative healing was uneventful, and no adverse effects related to the use of the EO + E were reported.…”
Section: In Vitro Wound Closure Following Mouthrinse Treatmentmentioning
confidence: 99%